The Influence of Work Discipline, Workload, and Organizational Culture on the Education Quality in Public Elementary Schools - Dania Putri; Ngasbun Egar; Ghufron Abdullah (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme)
This research investigates the influence of work discipline, workload, and organizational culture on the quality of education in public elementary schools in Patean District, Kendal Regency. The study employs a quantitative approach with an ex post facto and correlational design to examine the extent of influence these internal institutional factors exert on educational quality. The population consisted of 268 teachers and education personnel, from which 160 respondents were selected using proportional random sampling. Data were collected through a structured questionnaire based on a Likert scale and analyzed using multiple linear regression through SPSS version 27. The results revealed that all three independent variables, work discipline, workload, and organizational culture, significantly and positively affect education quality, both partially and simultaneously. Among the variables, organizational culture demonstrated the strongest influence, indicating that schools with a collaborative, result-oriented, and stable culture are more likely to achieve high educational quality. Work discipline and workload also play essential roles in shaping teacher performance and daily school operations. The regression model explained 45.2% of the variance in educational quality. These findings confirm that improving school quality is not only dependent on external interventions such as curriculum or policy reforms, but is also significantly influenced by internal behavioral and cultural dynamics. Therefore, the study recommends that school leaders focus on strengthening organizational culture, enhancing professional discipline, and managing workloads effectively to promote sustainable improvements in educational outcomes.